Medical-nursing integrated service model in ophthalmic outpatient care for intravitreal injections: a retrospective cohort study - Lan, Genyin; Li, Zhuoxin; Cheng, Wenhui; Huang, Ruiyu; Guo, Yanxia; Yang, Xiaofang; Zhang, Baolu (Frontiers in Medicine, 2025)
BackgroundOutpatient intravitreal injections are widely utilized in contemporary ophthalmology practice. However, fragmented medical-nursing coordination and compressed clinical pathways challenge treatment standardization and compromise patient outcomes. This study aimed to evaluate the effectiveness of an integrated medical-nursing service model compared to conventional separated care in patients undergoing outpatient intravitreal injections.MethodsA retrospective cohort study was conducted involving 1,432 patients undergoing outpatient intravitreal injections at our hospital's ophthalmology department. Patients were divided into two groups: a control group (n = 631) receiving conventional separated medical and nursing care and an intervention group (n = 801) experiencing an integrated medical-nursing service model. Key outcome measures included patient satisfaction, correct usage rates of preoperative antibiotic eye drops, standardized treatment rates, vision-related quality of life using NEI-VFQ-25 scores, and complication rates.ResultsCompared with the control group, the intervention group showed significantly higher patient satisfaction (P < 0.001), higher correct usage rates of preoperative antibiotic eye drops (P < 0.001), higher standardized treatment rates (P < 0.001), and improved NEI-VFQ-25 scores (P < 0.001). Additionally, the intervention group experienced significantly lower rates of complications, including subconjunctival hemorrhage (1.12% vs. 5.71%), postoperative intraocular pressure elevation (0.25% vs. 3.33%), and infectious conjunctivitis (0.50% vs. 3.65%), all with P < 0.001.ConclusionsThe medical-nursing integrated service model significantly improves patient satisfaction, medication compliance, standardized treatment rates, and vision-related quality of life and reduces complications in outpatient intravitreal injections procedures. These findings suggest that this model effectively addresses key challenges in outpatient procedure delivery while enhancing both clinical outcomes and patient experience.